The Effect of Working Alliance on Online Counseling Settings in Lowering Anxiety Levels - Hafnia Rahma Alifa; Suci Nugraha; Endah Nawangsih (Eduvest - Journal of Universal Studies, 2025)
Telepsychology in Indonesia can be a solution to overcome the shortage of mental health professionals to address psychological problems, but it is a new challenge for counselors. Anxiety clients prefer online psychology services because of 1) easier access to feel accompanied by them when they are anxious and 2) they need immediate help in the event of a panic or anxiety attack. The public's interest in using telepsychology has not been accompanied by empirical data on the ability of counselors to provide online counseling services, especially in establishing working alliances. This research is the second stage. The first phase of research was conducted on 93 counselors who were selected through a simple random sampling technique. The result is that it is difficult for counselors to carry out extra therapy influence when conducting online counseling. This second research began by developing a way to increase extra therapy influence through monitoring tasks based on the principle of constructing tasks (Kazantzis et al., 2005) and monitoring tasks via text (Alfonsson et al., 2019) to overcome the difficulties of counselors in monitoring task assignments and conducting a test of the influence of the provision of monitoring modules structured in an online counseling setting to lower anxiety levels. The design of this second study is an equivalent comparison group design, with a total of 6 participants obtained through the purposive sampling technique.